2023
DOI: 10.3390/toxins15110644
|View full text |Cite
|
Sign up to set email alerts
|

Field Evaluation of Cotton Expressing Mpp51Aa2 as a Management Tool for Cotton Fleahoppers, Pseudatomoscelis seriatus (Reuter)

Brady P. Arthur,
Charles P. Suh,
Benjamin M. McKnight
et al.

Abstract: The cotton fleahopper (Pseudatomoscelis seriatus Reuter) is considered a highly economically damaging pest of cotton (Gossypium hirsutum L.) in Texas and Oklahoma. Current control methods rely heavily on the use of foliar-applied chemical insecticides, but considering the cost of insecticides and the critical timeliness of applications, chemical control methods are often not optimized to reduce potential yield losses from this pest. The Bacillus thuringiensis (Bt) Mpp51Aa2 (formerly Cry51Aa2.834_16) protein ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…Adult and nymph feeding damage on the ThryvOn cotton appeared to be negligible in the no-choice assay. These findings align with the observations by Arthur et al [35], where significantly higher square retention was found in ThryvOn cotton compared to a gene-lacking cultivar among diverse cotton fleahopper population densities across multiple years in the field. These results suggest that, even under forced conditions, cotton fleahoppers did not cause significant damage to ThryvOn cultivars.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Adult and nymph feeding damage on the ThryvOn cotton appeared to be negligible in the no-choice assay. These findings align with the observations by Arthur et al [35], where significantly higher square retention was found in ThryvOn cotton compared to a gene-lacking cultivar among diverse cotton fleahopper population densities across multiple years in the field. These results suggest that, even under forced conditions, cotton fleahoppers did not cause significant damage to ThryvOn cultivars.…”
Section: Discussionsupporting
confidence: 91%
“…This could potentially be explained by the high levels of infestation used in this study. As shown by Arthur et al [35], cotton expressing the Mpp51Aa2 protein suffered a significant square loss when exposed to high populations of cotton fleahoppers. Previous research has consistently concluded that ThryvOn cotton can deter the feeding of various insect pests of cotton, including tobacco thrips (Frankliniella fusca Hinds), western flower thrips (Frankliniella occidentalis Pergande), onion thrips (Thrips tabaci Lindeman), tarnished plant bugs, western tarnished plant bugs, and cotton fleahoppers [18,36,37].…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Renowned for its remarkable protein synthesis machinery, B. thuringiensis synthesizes a diverse array of insecticidal proteins, including Cry, Cyt, Vip, Vpa/Vpb, and Sip, each exhibiting a high specificity against various insect orders [2]. The integration of genes encoding these insecticidal proteins into crops, known as Bt crops, imparts targeted resistance against insect pests [3].…”
Section: Discussionmentioning
confidence: 99%